El fortalecimiento de los lazos familiares como contrapeso a la ausencia de relaciones sociales con la comunidad: el caso de las familias migrantes peruanas en Japón - Nakamura Goshima, Patricia (2010)
A common problem that immigrants who arrive to different countries of the world face is finding information, guidance and support related to the education of their children. Generally, social networks formed by other fellow nationals represent an important source of support. However, a question arises from that premise. What happens in the case of immigrants who do not have these kinds of connections with their fellow nationals? This paper analyses the case of a Peruvian community in Japan where a lack of strong relationships that represent a valuable social capital for its members was observed. As a consequence, the families are compensating this deficit through a strengthening of their family bonds, while their children become the main source of information regarding the Japanese educational system